Leadership and Management: Locating the Concepts - Inom Nasution; Taufik Hidayat (Tarbiatuna: Journal of Islamic Education Studies, 2024)
Nowadays, every individual is aware of the importance of knowledge as a guide/tool/guide to lead humanity which is increasingly large in number and has complex problems. It is based on this awareness and is relevant to the learning process which requires every human being to seek knowledge. Judging from the type of research, there is also a type of research used in this research, namely bibliography research or library research, namely research that is carried out by collecting information or objective note-taking which is aimed at the object of research or gathering information in the form of a bibliography, or analysis carried out to uncover a problem which is basically focused on a critical and in-depth study of relevant library materials. Thus, this effort cannot be separated from education, and educational goals will not be achieved optimally without good educational management or management, which is further in Educational management activities require a leader who has the ability to become a leader.